Speech Repair and Classroom Interaction Strategies to Enhance Students English Language Skills at the University of Muhammadiyah Surakarta - Guswantoro, Kwica; Laila, Malikatul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to identify the speech repair strategies employed by students and lecturers during classroom interaction to enhance English language competence. Methodology: This research applies a descriptive qualitative method, using Conversation Analysis (CA) to examine the verbal interactions between students and lecturers. Data were collected through observations and recordings of classroom activities in Fiction class with 60 total students combined from both classes, focusing on the patterns of turn-taking and speech repair. The analysis employs (Liddicoat, 2007) repair strategy framework to categorize different types of repairs (self-initiated self-repair, self-initiated other-repair, other-initiated self-repair and other-initiated other-repair). Results: The findings revealed that self-initiated self-repair was the most frequently employed strategy, highlighting the importance of learner autonomy and active engagement in the language learning process. The findings highlight a variety of speech repair strategies used by students and lecturers in these interactions, showing how they contribute to improving English language proficiency. Applications/Originality/Value: Specifically, methods like self-initiated and other-initiated corrections raise students' linguistic awareness and facilitate more effective error correction, leading to stronger communication skills and overall language improvement.